ChemInform Abstract: Bifunctional Chiral Dehydroalanines for Peptide Coupling and Stereoselective S‐Michael Addition. Issue 44 (13th October 2016) - Gutierrez‐Jimenez, Marta I.; Aydillo, Carlos; Navo, Claudio D.; Avenoza, Alberto; Corzana, Francisco; Jimenez‐Oses, Gonzalo; Zurbano, Maria M.; Busto, Jesus H.; Peregrina, Jesus M.
Abstract: The chiral bicyclic dehydroalanine building block (I) is applied in stereoselective S‐Michael reactions with a variety of thiols.